Build it and They Will Come: Building the Capacity of Indigenous Units in Universities to Provide Better Support for Indigenous Australian Postgraduate Students - Trudgett, Michelle (The Australian Journal of Indigenous Education, 2009)
Abstract Indigenous participation rates in higher education are significantly lower than the rates reported for non-Indigenous people in Australia – with the greatest disparity evident in the area of postgraduate studies. This problem needs to be addressed by providing culturally appropriate support mechanisms to Indigenous postgraduate students. This article draws on the findings of a doctoral thesis in which the support provided to Indigenous postgraduate students in Australia was investigated (Trudgett, 2008). Several issues and problems emerged from the data surrounding the support, or lack thereof, provided to this cohort by the Indigenous Units or centres in universities today. Nine recommendations for consideration and implementation by the Indigenous Units within Australian universities are provided. These recommendations have the potential to reduce this disparity by helping to close the gap between Indigenous and non-Indigenous participation and, most importantly, completion rates in postgraduate studies.